A Scoping Review of the Role of Wildlife in the Transmission of Bacterial Pathogens and Antimicrobial Resistance to the Food Chain. (30th August 2014) - Greig, J.; Rajić, A.; Young, I.; Mascarenhas, M.; Waddell, L.; LeJeune, J.
Summary Wildlife can contribute to environmental contamination with bacterial pathogens and their transfer to the human food chain. Global usage and frequent misuse of antimicrobials contribute to emergence of new antimicrobial resistant (AMR) strains of foodborne pathogens. We conducted a scoping review of published research to identify and characterize the evidence on wildlife's role in transmission of AMR and/or bacterial pathogens to the food chain. An advisory group (AG) of 13 North American experts from diverse disciplines was surveyed to solicit insight in the review scope, priority topics and research characteristics. A pre‐tested search strategy was implemented in seven bibliographic databases (1990 to January 2013). Citations were relevance screened, and key characteristics on priority topics extracted independently by two reviewers. Analysis identified topic areas with solid evidence and main knowledge gaps. North America reported 30% of 866 relevant articles. The prevalence of five targeted bacterial pathogens and/or AMR in any pathogen in wildlife was reported in 582 articles. Transmission risk factors for selected bacteria or AMR in any bacteria were reported in 300. Interventions to control transmission were discussed in 124 articles and formally evaluated in 50. The majority of primary research investigated birds, cervids, rodents, feral pigs, opossums, E. coli (n = 329), Salmonella (n = 293) and Campylobacter (n = 124). An association between wildlife and transmission of bacterial pathogens and/or AMR to the food chain was supported in 122 studies. The scoping review identified a significant body of research on the role of wild birds in the prevalence and transmission of E. coli, Salmonella and Campylobacter. There was little research employing molecular methods contributing to the evidence concerning the importance and direction of transmission of wildlife/pathogen combinations. Given the advancements of these methods, future research should focus in this area to help prioritize future intervention studies and risk mitigation strategies.